Morphological characteristic of calcium carbonate nanoparticles derived from blood cockle shells (Anadara granosa) - Mohd Thani, Suryati; Sa’at, Azmah; Abas, Razif; Mohamad Zainal, Nurul Hayati; Mohd Moklas, Mohamad Aris; Mohamad Yusof, Loqman; Mohd Thani, Nurfatimah; Abu Bakar @ Zakaria, Md Zuki (Universiti Putra Malaysia Press, 2023)
Blood cockle shells are a type of shellfish with distinctive bright red color that is commonly found in coastal areas of Asia, a rich source of protein, vitamins, and minerals, including calcium carbonate. Calcium carbonate (CaCO3) is a common mineral supplement that slowly paved its way into nano research to support bone health that also used in the treatment of bone infections due to its inherent properties; reduces inflammation, promotes bone healing, crucial role in the immune system, and slow degradability. The latest invention on CaCO3 from cockle shells, is an alternative mode of drug delivery to circumvent existing antibiotic resistance mechanisms and allow direct drug delivery to the target site, using locally sourced ingredients to reduce long-term high production costs. A top-down approach CaCO3 nanoparticles from blood cockle (Anadara granosa) shells were developed, known as calcium carbonate nanoparticles (CNPs). This research aims to characterize the morphology of CNPs from blood cockle shells via Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), and Atomic Force Microscopy (AFM). Results:A homogeneously spherical CNPs. with a mean diameter of 36.5 ± 2.3 nm was observed on TEM, so as FESEM. From AFM, the mean diameter for CNPs was 38.6 ± 3.6 nm The CNPs were spherical in shape, homogenously scattered, less agglomerate, porous with rough surfaces. The size and morphology of the CNPs from blood cockle shells were suitable for transport carrier in situ bone infection, according to the results.